PENANAMAN PERILAKU EMPATI MELALUI ROLE PLAYING PADA ANAK - Muh. Fitrah Ramadhan Umar; Nur Aulia Saudi; Sitti Syawaliah Gismin (Nusantara Hasana Journal, 2022)
Humans are social creatures who cannot live without other people. We as humans are asked to be able to understand each other's feelings. This condition is usually called empathy. Maclsaac (1997) in his book suggests that empathy is an individual process that thinks about the condition of other individuals as if we were in that person's position. When someone has empathy, it means that person is putting them in someone else's position and learning to understand others. This study uses a systematic literature review method. The results of this study suggest that instilling empathetic behavior through role playing in children has a considerable impact.